Structure of a photosynthetic reaction centre determined by serial femtosecond crystallography - Johansson, Linda; Arnlund, David; Katona, Gergely; White, Thomas A.; Barty, Anton; DePonte, Daniel P.; Shoeman, Robert L.; Wickstrand, Cecilia; Sharma, Amit; Williams, Garth J.; Aquila, Andrew; Bogan, Michael J.; et al. (Nature Communications, 2013)
Serial femtosecond crystallography is an X-ray free-electron-laser-based method with considerable potential to have an impact on challenging problems in structural biology. Here we present X-ray diffraction data recorded from microcrystals of the Blastochloris viridis photosynthetic reaction centre to 2.8 Å resolution and determine its serial femtosecond crystallography structure to 3.5 Å resolution. Although every microcrystal is exposed to a dose of 33 MGy, no signs of X-ray-induced radiation damage are visible in this integral membrane protein structure.